Monitoring of Overburden Failure with a Large Fractured-Height Working Face in a Deep Jurassic Coal Seam Based on the Electric Method - Rongxin Wu; Yuze Wu; Binyang Sun; Guanqun Zhou; Leilei Zheng (Applied Sciences)
The development height of a water-flowing fractured zone is the key parameter to consider when carrying out mining under water pressure and coal mining with water conservation. In this paper, Jurassic coal seam 3-1 in the Menkeqing Coal Mine was taken as the research target, and a three-dimensional mining geological model was established by using FLAC3D to study the deformation and failure rules of overburden. Three roof boreholes were drilled in the auxiliary transportation roadway of adjacent working faces for dynamic monitoring by the resistivity method, which can better observe the whole process from failure to stability of the overburden. The results show that due to the complex sedimentary environment and large buried depth of coal seams in western China, there is a large deviation between the calculation results of the empirical formula of the fractured zone height under the “Regulations of buildings, water, railway and main well lane leaving coal pillar and press coal mining” (three regulations) and the simulation and on-site measurement. Based on the comprehensive analysis, the influence range of mining advance abutment pressure is approximately 60 m. The height of the water-flowing fractured zone is approximately 106 m, and it is located at the interface between sandy mudstone and mudstone. The height of the caving zone is approximately 22 m, and it is located at the interface between fine sandstone and medium sandstone. The ratio of the fractured height and coal seam thickness (Rf) reached 24.4, which was basically consistent with the test result of the adjacent Yushenfu mining area (which was 26 on average). There is no obvious change in the development height of the caving zone and water-flowing fracture zone from the working face to the drilling borehole position of more than 120 m, which reflects that the height of the overburden failure zone is related to the control of lithological combination.